Future Giant Telescopes 2003
DOI: 10.1117/12.459868
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost of extremely large telescopes

Abstract: For future giant telescopes, control of construction and operation costs will be the key factor in their success. The best way to accomplish this cost control, while maximizing the performance of the telescope, will be through design-to-cost methods that use value engineering techniques to develop the most cost-effective design in terms of performance per dollar. This will require quantifiable measures of performance and cost, including: (1) a way of quantifying science value with scientific merit functions; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…In 2000, Bely indicated that a scaling law of 2.7 is considered the standard for ground-based observatories [8] and in 2002 Stepp stated that the consensus traditional scaling law appears to be 2.7. [9] While these laws are technically correct, they should not be extended to space telescopes because they all include the ground observatory building and/or dome (the cost of the dome is driven by the volume of the telescope which is proportional to D raised to the 3 rd power). And, space telescopes do not have domes.…”
Section: Ground Telescope Cost Modelsmentioning
confidence: 99%
“…In 2000, Bely indicated that a scaling law of 2.7 is considered the standard for ground-based observatories [8] and in 2002 Stepp stated that the consensus traditional scaling law appears to be 2.7. [9] While these laws are technically correct, they should not be extended to space telescopes because they all include the ground observatory building and/or dome (the cost of the dome is driven by the volume of the telescope which is proportional to D raised to the 3 rd power). And, space telescopes do not have domes.…”
Section: Ground Telescope Cost Modelsmentioning
confidence: 99%
“…Stepp et al [53] discuss that if one were to extrapolate from the Kitt Peak Mayall 4m to Keck I, the projected cost was 4 times more than the actual cost.…”
Section: Pos(bash11)011mentioning
confidence: 99%
“…Construction costs are not, in the end, the dominant cost of telescopes. Over the course of a 30 year lifetime, an intermediate sized telescope (4-10m) will cost two to three times its construction costs [53]. This is estimating the operating costs at 3 to 6 percent of the construction cost of the facility, and doesn't include instrument development.…”
Section: Pos(bash11)011mentioning
confidence: 99%
“…The tilt perturbations are introduced to each segment as a tilt of the parent mirror about its global origin. Tilting about the global origin also results in an inconvenient translation of the segment, as shown in Equation (1).…”
Section: Introducing Geometric Perturbationsmentioning
confidence: 99%
“…1 To simultaneously achieve cost and performance goals, all components of the telescope must be developed as part of an integrated system. The major tools supporting the design and realization of a Thirty Meter Telescope as a system are an integrated computer model capable of predicting the performance of the telescope, a parametric cost estimate capable of predicting the cost of the telescope, and a science merit function capable of linking the engineering performance and the cost of the telescope to the scientific goals and preferences of the relevant astronomical community.…”
Section: Introductionmentioning
confidence: 99%